Abortion in the first trimester: guideline of the DGGG (S2k-Level, AWMF Registry No. 015-094, December 2022) : part 2 with recommendations for surgical termination of pregnancy and follow-up care after termination of pregnancy = Schwangerschaftsabbruch im 1. Trimenon : Leitlinie der DGGG (S2k-Level, AWMF-Registernummer 015-094, Dezember 2022) : Teil 2 mit Empfehlungen zum operativen Schwangerschaftsabbruch und zur Nachbetreuung nach dem Schwangerschaftsabbruch - David, Matthias; Achtenhagen, Anne; Bamberg, Christian; Bormann, Cornelia; Felderhoff-Müser, Ursula; Groth, Sylvia; Hänel, Kristina; König, Klaus; Korell, Matthias; Michl, Susanne; Redler, Silke; Schleußner, Ekkehard; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Purpose: The aim was to develop evidence-based recommendations where possible. The guideline presents the medical principles and scientific evidence for indications, counselling of affected persons, performing terminations, the choice of method, and the care and monitoring of a terminated pregnancy up until week 12 + 0 of gestation p. c. Methods: In accordance with the requirements for an S2k-guideline, the contents of the guideline were drafted following a systematic search of the literature by a representative interdisciplinary group of experts. Guideline authors held several formal meetings under the auspices of the German Society for Gynaecology and Obstetrics (DGGG) during which the contents of the guideline were finalised and agreed upon. Recommendations: The guideline provides recommendations on the surgical termination of pregnancy and follow-up care after termination of pregnancy.
Gesehen am 05.03.2024